Prevalence of BRAF V600 in primary gliomas: a systematic review. (15th October 2021) - Andrews, Lily; Thornton, Zak; Saincher, Samir; Dawson, Sarah; Cheng, Vincent; Higgins, Julian; McAleenan, Alexandra; Kurian, Kathreena
Abstract: Aims: Glioma is a fatal disease that causes significant years of life lost to an individual. Mutations in the driver gene BRAF, such as the V600 alteration, may contribute to gliomagenesis in adults and children through abnormal signaling causing uncontrolled cell proliferation. The use of BRAF-inhibitor drugs including Vemurafenib and Dabrafenib have shown a favorable response in 48% and 50% of melanoma patients with BRAF V600 mutations respectively. BRAF inhibitors and MEK inhibitors have shown efficacy in certain paediatric gliomas in the recurrent setting. Despite the potential benefit of BRAF inhibitors, the prevalence of BRAF V600 within primary gliomas is not fully discovered. Some studies identify the prevalence to be over 50%, while others find the prevalence to be around 1%. We performed a comprehensive systematic review to determine the prevalence of BRAF V600 within the adult and paediatric glioma population in different diagnostic groups. Method: A systematic literature search was performed using Ovid MEDLINE and Embase from genesis to the 22nd October 2020. Studies were not restricted by language. Studies were eligible if patients were histologically diagnosed according to WHO guidelines as a primary glioma evaluating the prevalence of BRAF V600 and included ≥ 10 primary glioma patients. The review protocol was registered in PROSPERO (CRD42019127704). Search results were managed using Endnote. Two independent reviewers assessed the eligibility of the publications using Rayyan, conflicts were evaluated by a third reviewer. Included articles were extracted by one reviewer and confirmed by a second reviewer. Risk of bias assessments were conducted using Hoy et al's risk of bias tool. Results were synthesized using "metaprop" in R. The meta-analysis was carried out in R which produced forest plots. Results: Our cohort included 182 studies with a total of 13669 adult and paediatric glioma patients classified diagnostically according to WHO guidelines. Among 48 glioma entities, BRAF V600 was identified most commonly in epithelioid glioblastoma with a prevalence of 69% (95% confidence interval (CI): 45-89%), followed by pleomorphic xanthoastrocytoma with a prevalence of 56% (95% CI: 48-64%), anaplastic pleomorphic xanthoastrocytoma with a prevalence of 38% (95% CI: 23-54%), ganglioglioma with a prevalence of 40% (95% CI: 33-46%), and anaplastic ganglioglioma with a prevalence of 46% (95% CI: 18-76%). Other glioma entities were found to have a prevalence of BRAF V600, these include astroblastoma (24%), desmoplastic infantile astrocytoma (16%), subependymal giant cell astrocytoma (8%), dysembryoplastic neuroepithelial tumour (3%), diffuse astrocytoma (3%), and pilocytic astrocytoma (3%). Conclusion: To our knowledge, this is the largest systematic review examining the prevalence of BRAF V600 in adult and paediatric glioma classified according to diagnostic WHO criteria. However, there were some limitations in this review. The sample sizes of some studies were very small, and the method of mutational analysis for BRAF V600 varied between papers. We found BRAF V600 in a significant prevalence of epithelioid glioblastoma, pleomorphic xanthoastrocytoma, anaplastic pleomorphic xanthoastrocytoma, ganglioglioma, and anaplastic ganglioglioma. Of interest, BRAF V600 mutation was found in a lower prevalence of astroblastoma, desmoplastic infantile astrocytoma, subependymal giant cell astrocytoma, dysembryoplastic neuroepithelial tumour, diffuse astrocytoma, and pilocytic astrocytoma. Consideration of assessment of BRAF V600 mutation may enable further treatment options with BRAF and/or MEK inhibitors in these particular diagnostic entities.